RANCANG BANGUN PROTOTYPE PEMBANGKIT LISTRIK TENAGA MIKRO HIDRO MENGGUNAKAN TURBIN CROSS-FLOW - Andrean Wiranata, I Putu; Janardana, I Gusti Ngurah; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 7 No 4 (2020): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2020.v07.i04.p20, 2020)
Many hydropower plants today are built on a large scale. Meanwhile, the construction of this large-scale power plant requires a very large area and a very high head. This has an impact on the difficulty of distributing electrical energy to remote areas, on the other hand, there are still many small rivers in remote residential areas that have not been fully utilized as an alternative to potential sources of electricity generation. So to overcome this, through this research a prototype Micro Hydro Power Plant (PLTMH) was made using a Cross-Flow turbine which of course can be applied to rivers that have a fairly low flow and head. In this study, the results of the calculation of the PLTMH prototype parameters with a Cross-Flow Turbine were designed at an effective head of 6 meters. The design of the Cross-Flow Turbine uses a runner outer diameter of 0.15 meters, a runner inner diameter of 0.10 meters, and the number of blades is 18. The test results obtained 574,6 rpm of turbine rotation before coupled with the generator; 489 rpm rotation of the turbine after coupling the generator; 3309.2 rpm of turbine rotation, 36.52 V output voltage at no load, and 386.4 rpm maximum turbine rotation; 2584.4 rpm maximum generator rotation; 28.18 V maximum output voltage; 0.422 A maximum output current; 10.59 Watts of maximum output power; 0.312 Nm of maximum torque; 8,026% maximum efficiency at load.